Cover Story. (15th October 2019) - Gill, Chris; Vandergrift, Gregory
Abstract : Fentanyl and related analog compounds are currently at the centre of an international health crisis. While fentanyl is used safely and effectively as an analgesic in clinical settings, it has recently seen an unprecedented rise in illicit use. There are currently upwards of 1400 fentanyl analogues that have been synthesized to date, adding further complexity to the crisis in terms of both their relative toxicity and detection. The current health situation, termed the 'opioid crisis, ' has resulted in an astonishing and growing number of drug overdoses. The problem of the opioid crisis is complex, and the solutions are not immediately obvious. In this perspective special feature, Gregory Vandergrift and Chris Gill evaluate paper spray (PS) MS as a rapid, sensitive and quantitative method for trace fentanyl detection. Indeed, PS‐MS presents a simple yet effective analytical drug‐testing tool to aid in combatting the opioid overdose crisis. Dr. Chris Gill is Professor of Chemistry and co‐director of the Applied Environmental Research Laboratories at Vancouver Island University (Nanaimo, BC, Canada). His research interests include the development of ultra‐trace, direct MS methods for in situ and rapid measurements of trace analytes in complex environmental and bioanalytical samples.